Cross-cultural comparison of workplace stressors, ways of coping and demographic characteristics as predictors of physical and mental health among hospital nurses in Japan, Thailand, South Korea and the USA (Hawaii) - Lambert V.A. (2014)
In an attempt to cross-culturally compare factors that may contribute to the nursing shortage within countries that have produced a limited number of research findings on role stress in nurses, this research examined work stressors, ways of coping and demographic characteristics as predictors of physical and mental health among hospital nurses from Japan, South Korea, Thailand and the USA (Hawaii). Subjects (n=1554 hospital-based nurses) were administered four self-report questionnaires: Demographic Questionnaire, "Nursing Stress Scale", "Ways of Coping Questionnaire" and "SF-36 Health Survey". Findings suggested that nurses indicated similar workplace stressors, ways of coping, and levels of physical and mental health. While subjects, across countries, demonstrated a variety of predictors of physical and mental health, several predictors were found to be the same. Cross-culturally the role of nurses may vary; however, certain factors are predictive of the status of hospital nurses' physical health and mental health. © 2004 Elsevier Ltd. All rights reserved.